Efektivitas Pemanfaatan Serbuk Gergaji dan Limbah Media Tanam Jamur (Baglog) sebagai Bahan Baku Pembuatan Biogas - Dikdik Mulyadi; Lela Mukmilah Yuningsih; Desi Kusumawati (Syarif Hidayatullah State Islamic University, 2016)
Biogas is one of energy that can be produced by anaerobic fermentation of the organic compounds. The objective of this study was to determine the effectiveness of the utilization of waste of media mushroom growth (baglog) with sawdust as raw material for biogas with cow dung activators. The study was conducted through anaerobic fermentation of the samples containing waste baglog (sample 1) and sawdust (sample 2), with the addition of cow manure activator to each sample. Both of these samples do anaerobic fermentation for 32 days, then measuring the volume of biogas every 4 days for 32 days. Methane content in samples 1 and 2 measured by using gas chromatography. To see the effect of the addition of activators cow dung biogas volume measurement was carried out with cow dung without addition baglog waste and sawdust. The process of degradation baglog and sawdust with an activator of cow dung could be observed in some of the parameters through total solids (TS), total volatile solids (TVS), volatile fatty acids (VFA), the degree of acidity (pH), and C/N ratio. The results showed that effectiveness of sample 1 resulted in the everage of total volume biogas 28% higher than sample 2. The content of methane in sample 1 and sampel 2 was 54% %, and 0.21% respectively. The fermentation process biogas production in this experiment was carried out at pH 7, with a value of TS, TVS and VFA showed a decrease trend after the fermentation process, C/N ratiowas lower than the baglog waste sawdust until day 32 retention time. Keywords: Sawdust, baglog waste, biogas, fermentation, methane DOI : http://dx.doi.org/10.15408/jkv.v2i1.3100